2017
DOI: 10.3389/fnbeh.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Lateral Habenula in Pain-Associated Depression

Abstract: Patients with chronic pain have significantly higher incidences of depression and anxiety than the average person. However, the mechanism underlying this link has not been elucidated in terms of how chronic pain causes significant mood changes and further develops into severe anxiety or depression. The serotonergic system in the raphe nuclei is an important component in both pain processing and the pathogenesis of depression. Since the lateral habenular nucleus (LHb) controls the raphe nuclei, it may participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 48 publications
(65 reference statements)
5
60
0
2
Order By: Relevance
“…Among brain regions engaging the processing of pain information, the lateral habenula (LHb) is known to be activated by aversive stimuli and induces avoidance behavior [9,10]. Many studies have reported that the LHb in rodent and human is activated by noxious stimuli [11][12][13][14][15]. The lateral hypothalamic region (LHA) is directly innervated by sensory stimuli transmitted via spinothalamic tract, and directly projects to LHb.…”
Section: Main Textmentioning
confidence: 99%
“…Among brain regions engaging the processing of pain information, the lateral habenula (LHb) is known to be activated by aversive stimuli and induces avoidance behavior [9,10]. Many studies have reported that the LHb in rodent and human is activated by noxious stimuli [11][12][13][14][15]. The lateral hypothalamic region (LHA) is directly innervated by sensory stimuli transmitted via spinothalamic tract, and directly projects to LHb.…”
Section: Main Textmentioning
confidence: 99%
“…Monosynaptic viral vector tracing and electrophysiological studies have shown a variety of pathways from LHb to DR and median raphe, including glutamatergic projections to 5-HT neurons and GABAergic neurons, and that the LHb innervation of GABAergic DR neurons provides feedforward inhibition to 5-HT neurons (Pollack-Dorocic et al, 2014; Ogawa eta l., 2014; Zhou et al, 2017). These mechanisms by which the LHb regulates the serotoninergic DR and median raphe have been proposed to be involved in comorbidity of a variety of disorders with depression (Li et al, 2017; Wang et al, 2017; Zhang et al, 2016) and defensive behavior (Pobbe and Zangrossi, 2010). …”
Section: Efferent Connectionsmentioning
confidence: 99%
“…Furthermore, the connections between the Hb and raphe nuclei are especially important since the serotonergic system plays a role in both depression and pain ( Stamford, 1995 ; Gao et al, 2008 ). In animal models, lesions in the LHb produces a reduction in depressive-like behaviors by elevating the levels of serotonin in the dorsal raphe nucleus ( Yang et al, 2008 ), which strongly suggests the participation of the LHb in the control of pain-related depression ( Li et al, 2017 ). Supporting this notion, an increase in the LHb activity along with a reduced activity in the dorsal raphe nucleus has been found in an experimental model of neuropathic pain.…”
Section: An Overview Of the Reward System Elementsmentioning
confidence: 99%
“…Supporting this notion, an increase in the LHb activity along with a reduced activity in the dorsal raphe nucleus has been found in an experimental model of neuropathic pain. This model has also resulted in pain and depressive-like behaviors, which have been reversed by LHb lesions ( Li et al, 2017 ).…”
Section: An Overview Of the Reward System Elementsmentioning
confidence: 99%